Audit Rekam Medis dalam Upaya Peningkatan Kualitas Pengisian Rekam Medis di RSUD Sleman - Sugeng; Dian Herawati; Salim, Marko Ferdian (Akademi Perekam dan Informasi Kesehatan Imelda, 2024)
A hospital is a health service institution that provides complete individual health services for inpatient, outpatient, and emergency care. Hospitals as health service providers are required to maintain medical records. The administration of medical records for each hospital refers to the Regulation of the Minister of Health of the Republic of Indonesia. A medical record audit is needed to determine the completeness of data in medical records both in quantity and quality. The purpose of this study was to determine the medical record audit at RSUD Sleman. The type of research used is analytic observational with a cross-sectional study design. This research was conducted at RSUD Sleman, Special Region of Yogyakarta. The research was done from April to October 2022, during a period of 7 months. Simple random sampling was used to collect data from 94 medical records. The audit of 94 samples of medical records resulted in the following findings: completeness, patient identity 100%, professional identity in providing care 99.01%, date and time 70.21%, initial assessment 90.42%, subjective examination 98.84%, objective examination 66.01%, management plan 91.49%, clinical pathology examination 58.51%, radiological examination 75.53%, primary diagnosis 100%, secondary diagnosis 100%, and general agreement 100%. The lowest percentage of 58.51% was obtained for incomplete data.